P508 Does corticosteroid therapy affect prognosis in inflammatory bowel disease patients hospitalised with Clostridium difficile infection?. (25th January 2019) - Bar Yoseph, H; Daoud, H; Ben Hur, D; Chowers, Y; Waterman, M
Abstract: Background: Clostridium difficile infection (CDI) is a common infection among inflammatory bowel disease (IBD) patients admitted to the hospital and is associated with morbidity and mortality. While CDI therapy is mostly antimicrobial, acute IBD flares are often treated with corticosteroids (CS). Due to their immunosuppresive effect, CS therapy raises concern of worsening CDI outcomes. We aimed to assess the impact of CS therapy on outcomes of IBD patients hospitalised for flare-up and diagnosed with CDI. Methods: A retrospective single tertiary care centre cohort study of IBD patients admitted with first-time CDI between 2002 and 2018. Comparisons were made based on CS exposure during 48 h after admission. Patients with incomplete medical records on the index admission and non-definite diagnosis of IBD or CDI were excluded. The primary outcomes of the study were all-cause mortality or colectomy within 3 months. Other outcomes were diarrhoea improvement, length of stay, need for readmission, associated bacteraemia and 1 year colectomy and mortality rates. Cox proportional hazard model was used to assess the effects of CS use on survival by IBD subtype. Kaplan–Meier curves were used to estimate survival across time. Logistic regression was used to assess the effects of steroid use on the probability for adverse outcomes within 3 months. Univariate analysis with chi-square, Fisher or t -test and multi-variate analysis using different regression models were used to assess the effect of CS use on other variables. Results: 111 patients (62 CD, 46 UC, 3 IBDU) were included, 84 (75.6%)received CS. There were no significant differences in baseline IBD and CDI characteristics, demographics and medications use. At 3 months, 7 (3.6%) patients died. Four (5.4%) patients required colectomy (all exposed to CS), though CS association with colectomy was statistically insignificant (table). However, Bacteraemia and 1-year mortality rates were slightly but significantly reduced among CS exposed (figure and table). All other endpoints were not associated with CS exposure. 1-year colectomy and mortality-free survival. Conclusions: CS exposure during the first 48 h after admission for flaring IBD patients with CDI was not associated with adverse outcomes. Albeit the largest cohort to published to date, the low rates of adverse outcomes observed still preclude deduction of definite conclusions. Larger studies are required.